Exploring Links between Reparations and Development: A Comparative Case Study in Peru - Koningh, Ingeborg de (Student Undergraduate Research E-journal!, 2017)
Links between reparations and development have theoretically been explored in current literature, however claims have hardly been assessed empirically. This paper provides such assessment through a comparative case study in three departments of Peru from 2007 to 2014. Subject of investigation is the national reparations programme, the Programa Integral de Reparaciónes (PIR). It is hypothesised that this programme helped improve social integration, reduce poverty and improve higher educational and health outcomes. While strongly tentative, results suggest that reparations programmes may be linked to improvements in living standards.